Oblikovanje in izdelava polirne naprave ter polirni postopek z uporabo materiala Al 7075 T6 - Başak, Hüdayim (Strojniški vestnik, 2007)
The burnishing process is a final process that can also be described as a chipless process. In this paper, burnishing equipment that is designed and manufactured for the burnishing of prismatic parts is introduced. This burnishing equipment was then used to burnish prismatically manufactured Al 7075 T6 samples using different burnishing parameters. The burnished surfaces were characterized in terms of roughness and hardness.
Keywords: poliranje; površine; hrapavost; trdota